Terminal efficiency, lag and dropout in cohorts from 2007 to 2014 of dental students at the University of Costa Rica = Eficiencia terminal, rezago y abandono en las cohortes del2007 al 2014 de estudiantes de Odontología de laUniversidad de Costa Rica - Castro Sancho, Cristina 1970-; Gómez Fernández, Adrián José 1980-; Fantin, Romain Clement 1988-; Gutiérrez Marín, Natalia 1975- (2023)
Determine the terminal efficiency, lag and dropout in the cohorts of students who entered the dentistry career at the Faculty of Dentistry at University of Costa Rica in the lapse 2007 to 2014. Data from 736 files were collected. The variables considered were sex, admission age, nationality, marital status, children, admission note, domicile and high school. The data was collected from the Student Application System, the physical files, and the data base from the Supreme Court of Elections of Costa Rica. Descriptive statistics, bivariate and multivariate analysis were made, which were implemented from two logistic regression models. 98% of the students were Costa Rican, 68% women, 79% entered according to the admission note, 43% entered with an age of 18 years or less, 50% came from a public school, 77% resided in the Greater Metropolitan Area and 95% were single and remained without children. The average terminal efficiency was 6%; 46% of students have graduated with lag, 16% are still enrolled and 32% dropped out. Sex, age, admission note, and motherhood are sociodemographic variables that are associated with terminal efficiency and dropout. The average terminal efficiency in the cohorts from 2007 to 2014 in the courses at the Faculty of Dentistry University of Costa Rica was very low, almost half of the students graduated with lag and about a third dropped out the studies. The grade from the admission note seems to be a predictor of students' academic behavior, higher grade had more chances of graduating and less likely to dropout.
Determinar la eficiencia terminal, el rezago y el abandono en las cohortes de los estudiantes que ingresaron a la carrera de Odontología de la Facultad de Odontología UCR en el período 2007 al 2014. Se recopilaron los datos de 736 expedientes. Las variables consideradas fueron: sexo, edad de ingreso, nacionalidad, estado civil, hijos, lugar y colegio de procedencia, y nota de examen de admisión. Los datos se recopilaron del Sistema de Aplicaciones Estudiantiles, los expedientes físicos y del Tribunal Supremo de Elecciones de Costa Rica. Se realizó estadística descriptiva, análisis bivariado y multivariado que se implementó a partir de dos modelos de regresión logística. El 98% de los estudiantes fueron costarricenses, el 68% mujeres, el 79% ingresó según la nota de admisión, el 43% ingresó con una edad de 18 años o menos, el 50% provenía de un colegio público, el 77% residía en la gran área Metropolitana y el 95% eran solteros y permanecieron sin hijos. La eficiencia terminal en promedio fue de 6%; el 46% de los estudiantes se han graduado con rezago, el 16% continúan matriculados y el 32% hizo abandono de los estudios. El sexo, la edad, la nota del examen de admisión y la maternidad son variables sociodemográficas que se asocian con la eficiencia terminal y el abandono. El promedio de la eficiencia terminal en las cohortes del 2007 al 2014 en la carrera de Odontología de la Facultad de Odontología UCR fue muy bajo, casi la mitad de los estudiantes se han graduado con rezago y cerca de un tercio hizo abandono de los estudios. La nota del examen de admisión parece ser un predictor en el comportamiento académico de los estudiantes: a mayor nota más posibilidades de graduarse y menos de abandonar la carrera.
En revista Odóvtos, vol. 25, no.3 (septiembre-diciembre 2023)
Descripción basada en el contenido visto el 21 de enero, 2025
También disponible en formato HTML y EPUB
Texto también en español